The development of employee attendance application based on mobile using spiral method - Muhamad Alda (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The Pangulu Nagori Amborokan Panei Raya Office is one of the governmental institutions tasked with serving the local population. The Pangulu Nagori Amborokan Panei Raya office still records employee attendance using the manual approach. Employee attendance is noted in the attendance book. When done this way, there are still issues that come up. Particularly the time and effort put forth to complete the attendance procedure. In addition, because attendance data has very little protection and is accessible to anyone, it is challenging to summarize staff attendance reports. Building an Android-based application that can be used to process and track employee attendance is the aim of the author's research. The author employs UML to visually create the application design (Unified Modeling Language). The system development methodology, however, is a spiral that includes the phases of customer evaluation, planning, risk analysis, engineering, building, and disposal. The Kodular framework and the Airtable database are used in the development of an Android-based attendance application. The results of the study are an android-based attendance application that can be applied to make it easier for employees to take attendance and monitor employee attendance in real-time using an Android smartphone.